Soft Skills Guru Berbasis Keteladanan Nabi Muhammad SAW - Fibririn Corina Rambe; Zulhamri (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
The Prophet Muhammad SAW was a rabbinic teacher with character, who planted the seeds of love before starting to teach, who considered his students as brothers or children before he became his teacher. Prophet Muhammad SAW, both Inter-personal skills and Intra-personal skills as a teacher who should be followed by a teacher, to become the same character at least approaching that character. The example of the Prophet Muhammad SAW was very influential in teaching Muslims, making Muslims have a good culture, balancing behavior, and leading to the formation of an Islamic personality and an Islamic society. The character of the Prophet Muhammad is a role model who displays the Qur'an and embodies the contents of the Qur'an into actions, behavior, relationships, and thoughts and feelings. Prophet Muhammad SAW has soft skills that should be imitated by teachers in every development of Islamic Religious Education learning.